Preparation and characterization of vemurafenib microemulsion - Neamah, Mohammed Jassim; Entidhar J. Al-Akkam (Iraqi Journal of Pharmaceutical Sciences, 2023)
Human melanoma is the most common and malignant type of skin cancer. Vemurafenib has been used for the treatment of malignant or metastatic melanoma. Oral vemurafenib has serious adverse drug reactions includingQTc sigment prolongation of heart ECG that may result in discontinuation of treatment. The aim of study was to prepare o/w vemurafenib microemulsion to be used for topical administration. Saturated solubility of vemurafenib were performed in different oils, surfactants and co-surfactants. Peppermint oil, Tween 20 and PEG 400 were chosen to be the oil phase, surfactant and co-surfactant repectively. Since, vemurafenib had the highest solubility in these materials. Six fromulas (F1- F6) of vemurafenib microemulsion were prepared by simple titration method and characterized for their particle size, polydipersity (PDI), zeta potential, microemulsion morphology, dilution test, conductivity, thermodynamic stability and drug release. Formula F3 was chosen since it exhibits the lowest particle size (11.83 nm ± 0.55 nm), zeta potential -2.57 mV, passed the thermodynamic stability tests and had significantly higher (P < 0.05) release percent for vemurafenib (91% within 24 h). As a conclusion, microemulsion is considered as a poweful and promising drug delivery system for topical administation